A dual-stream model based on PRNU and quaternion RGB for detecting fake faces - Mohan Hua; Shuangliang Li; Jinwei Wang (PLoS ONE, 2025)
The forensic examination of AIGC(Artificial Intelligence Generated Content) faces poses a contemporary challenge within the realm of color image forensics. A myriad of artificially generated faces by AIGC encompasses both global and local manipulations. While there has been noteworthy progress in the forensic scrutiny of fake faces, current research primarily focuses on the isolated detection of globally and locally manipulated fake faces, thus lacking a universally effective detection methodology. To address this limitation, we propose a sophisticated forensic model that incorporates a dual-stream framework comprising quaternion RGB and PRNU(Photo Response Non-Uniformity). The PRNU stream extracts the “camera fingerprint” feature by discerning the non-uniform response of the image sensor under varying lighting conditions, thereby encapsulating the overall distribution characteristics of globally manipulated faces. The quaternion RGB stream leverages the inherent nonlinear properties of quaternions and their informative representation capabilities to accurately describe changes in image color, background, and spatial structure, facilitating the meticulous capture of nuanced local distinctions between locally manipulated faces and real faces. Ultimately, we integrate the two streams to establish the exchange of feature information between PRNU and quaternion RGB streams. This strategic integration fully exploits the complementarity between two streams to amalgamate local and global features effectively. Experimental results obtained from diverse datasets underscore the advantages of our method in terms of accuracy, achieving a detection accuracy of 96.81%.